Migratory Sheep Farming Practices in Cauvery Delta Zone in Tamil Nadu - Kannadhasan, MS; Chander, Mahesh; Bardhan, D (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Migratory sheep, due to its movement, poses threat of spreading diseases among small ruminants. Considering this, the study was carried out to identify the focus area of extension intervention among the migratory sheep farmers to disseminate scientifically recommended practices which minimize disease risk and enhance flock health. The study was conducted following ex post fact research design at Venganur village, Cuddalore district, Tamil Nadu. Using a semi-structured interview schedule, data were personally collected from 30 migratory sheep farmers who were selected purposively. The findings were subjected to focussed group interview involving seven farmers. The results envisaged a wider difference among the farmers from 100 per cent non-adoption of balanced ration to 100.00 per cent adoption of deworming. Therefore, extension interventions need to be intensified to educate the farmers on technologies which help in disease prevention and control.